O Brasil de Mr. Slang: a República nas crônicas de Monteiro Lobato (1926-1927) - MOTA, Danyllo Di Giorgio Martins da (2010)
The Revolution of 1930 became a landmark of Brazilian historiography on Republic. Affirmed as the inauguration of a moment of modernism in Brazil, its analysis was guided by the counterpoint to the First Republic, seen as a symbol experience failure and lack of modernization projects. However, a most recent historiography has approached the 1920s as a time independent of the movement, examining aspects of modernizing projects developed during this period. One of these perspectives of modernity and modernization present in the First Republic is related to the state of Sao Paulo, whose Clues can be identified in the work of Monteiro Lobato. The representation of St. Paul as a place of work, modernity and progress has become element fundamental to the affirmation of the state as a symbol for the nation to follow. This perspective, termed Paulistania, is expressed in the book and Mr. Slang Brazil comprising chronic Lobato produced over 1926. The texts present the author's view of the Brazilian Republic in a time of transition policy in which St. Paul took over the control of central power with the Republican Washington Luis election for the presidency. Discussions on politics and economics developed by Lobato reveal the purpose of forming an opinion favorable to the government in Washington Luis, whose task would be to promote the progress and national modernization in the mold of São Paulo. Similar to the discourse on the Age Vargas emerged in 1930, Monteiro Lobato in 1926 builds the image of new government, led by Sao Paulo as a symbol of breaking with the period crisis facing the Republic, called cyclonic period, indicating the expectation of a new Brazil.